2012
DOI: 10.3857/roj.2012.30.3.146
|View full text |Cite
|
Sign up to set email alerts
|

The impact of beam angle configuration of intensity-modulated radiotherapy in the hepatocellular carcinoma

Abstract: PurposeThis treatment planning study was undertaken to evaluate the impact of beam angle configuration of intensity-modulated radiotherapy (IMRT) on the dose of the normal liver in hepatocellular carcinoma (HCC).Materials and MethodsThe computed tomography datasets of 25 patients treated with IMRT for HCC were selected. Two IMRT plans using five beams were made in each patient; beams with equidistance of 72° (Plan I), and beams with a 30° angle of separation entering the body near the tumor (Plan II). Both pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In recent years, many guidelines for the management of HCC have been published throughout the world. [19][20][21] Surgical resection of HCC is the treatment of choice, while a treatment option for unresectable HCC involves RT alone or in combination with other therapies. 18 RT is a major treatment for many types of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many guidelines for the management of HCC have been published throughout the world. [19][20][21] Surgical resection of HCC is the treatment of choice, while a treatment option for unresectable HCC involves RT alone or in combination with other therapies. 18 RT is a major treatment for many types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that current RT technology, including intensity-modulated RT, image-guided RT and helical tomotherapy may be effective against HCC as well as prostate cancer and neck and head cancer. [19][20][21] Surgical resection of HCC is the treatment of choice, while a treatment option for unresectable HCC involves RT alone or in combination with other therapies. 18 The current RT technology with the accurate spatial and temporal variation of irradiation allows a higher dose of radiation than the conventional dose without affecting normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, several alternative modalities of surgery such as transarterial chemoembolization, percutaneous ethanol injection, radiofrequency ablation, sorafenib, or radiotherapy (RT) have been used [ 2 3 4 5 6 7 ]. Although recent advances in RT techniques including intensity-modulated radiation therapy (IMRT), volumetric modulated arc therapy (VMAT), and stereotactic body radiation therapy (SBRT) have augmented the role of RT in HCC [ 6 7 8 9 10 11 12 ], in the past, RT had a limited role because of the high risk of liver toxicities such as radiation-induced liver disease (RILD), which is believed to be an almost fatal complication once it occurs [ 13 14 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sung et al. found that the exposure dose to normal liver tissue of IMRT plans for five adjacent uneven fields was less than that of IMRT plans for five equational fields surrounding the target . Therefore, K‐IMRT should be used for the optimization of IMRT plans, and the field angle should be set manually by the radiotherapy physicist, according to the four basic principles of field angle and treatment experience.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Sung et al found that the exposure dose to normal liver tissue of IMRT plans for five adjacent uneven fields was less than that of IMRT plans for five equational fields surrounding the target. 19 Therefore, K-IMRT should be used for the optimization of IMRT plans, and the field angle should be set manually In conclusion, K-IMRT is an application of big data. It can be trained using the radiotherapy plans of therapeutic patients and then used to optimize the radiotherapy plans of new patients.…”
Section: Discussionmentioning
confidence: 99%